(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
In this study, AgGaSe2 (AGS) thin films were formed onto cleaned glass substrates by using the stacked elemental layer (SEL) deposition technique in vacuum. The films were prepared at the post-deposition annealing temperature from 100 to 350°C for 15 min duration. The atomic composition of the films was measured by energy dispersive analysis of X-ray (EDAX) method. The films ascertain the compositional uniformity. The X-ray diffraction (XRD) has been employed to study the structure of the films. The structures of the films are found to be polycrystalline in nature. The lattice parameters, grain size, strain and dislocation densities of the films were calculated. Optical characteristics of the films were ascertained by spectrophotometer in the photon wavelength ranging between 300 and 2500 nm. The transmittance was found to increase with the increase of annealing temperature. The transmittance falls steeply with decreasing wavelength. It revealed that AGS films have considerable absorption throughout the wavelength region from 400 to 800 nm. The optical band gap energy has been evaluated. Two possible direct allowed and direct forbidden transitions have been observed for all the AGS films in visible region. The former varied from 1.67 to 1.75 eV and the later from 2.05 to 2.08 eV, depending on the post-deposition annealing temperature of the films. DOI: 10.3329/jbas.v33i2.4101 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 179-188, 2009